Where art thou pituitary? - Ingle, Vaibhav (BMJ Case Rep, 2016)
A middle-aged woman presented with premature menopause and recurrent episodes of vomiting with hyponatraemia. Since primary causes of hormone deficiencies were the only studies initially evaluated, there was a delayed diagnosis. Pituitary tropic hormones (serum thyroid stimulating hormone/follicle stimulating hormone/luteinising hormone), inappropriately low for low-level of target hormones (free thyroxin/oestradiol), led to detailed evaluation of trophic hormone deficiencies by pituitary stimulation. The pituitary stimulation by insulin challenge test confirmed secondary (pituitary) hypofunction. Pituitary imaging revealed an uncommon cause of hypopituitarism, which is discussed in this case report.